2010
DOI: 10.1111/j.1365-263x.2010.01052.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health and 22q11 deletion syndrome: thoughts and experiences from the parents’ perspectives

Abstract: Parents not only described their children's oral health as important but also hard to gain. Thus, it is important that all patients with disabilities, regardless of whether there is a defined medical diagnosis or not, are identified and well taken care of in the dental care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 31 publications
0
30
0
1
Order By: Relevance
“…Thirteen studies revealed negative and positive emotions experienced amongst families, caregivers, and patients (Bales et al, 2010a; Briegel et al, 2008; Chan et al, 2015; Costain et al, 2012; Goodwin, Alam, et al, 2017; Goodwin & Mccormack, 2017; Goodwin, McCormack, et al, 2017; Hercher & Bruenner, 2008; Karas et al, 2014; Klingberg et al, 2010; Okashah et al, 2015; Phillips et al, 2017; Reilly et al, 2015). Three subthemes were identified: emotions experienced by parents and caregivers, emotional experiences faced by siblings, shared emotional experiences.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirteen studies revealed negative and positive emotions experienced amongst families, caregivers, and patients (Bales et al, 2010a; Briegel et al, 2008; Chan et al, 2015; Costain et al, 2012; Goodwin, Alam, et al, 2017; Goodwin & Mccormack, 2017; Goodwin, McCormack, et al, 2017; Hercher & Bruenner, 2008; Karas et al, 2014; Klingberg et al, 2010; Okashah et al, 2015; Phillips et al, 2017; Reilly et al, 2015). Three subthemes were identified: emotions experienced by parents and caregivers, emotional experiences faced by siblings, shared emotional experiences.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies highlighted emotional conflicts experienced by families and caregivers of individuals with 22q11DS, such as feelings of loss, grief, and guilt (Bales et al, 2010a; Briegel et al, 2008; Goodwin, Alam, et al, 2017; Goodwin & Mccormack, 2017; Goodwin, McCormack, et al, 2017; Hercher & Bruenner, 2008; Klingberg et al, 2010; Okashah et al, 2015). Parents’ reflections on what life could be like without 22q11DS raised feelings of grief, such as their child losing out on the milestones that a “normal” child is expected to have (Goodwin & Mccormack, 2017; Goodwin, McCormack, et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations